“Oman’s coast relations with Indonesia, Malaysia, China and India, and the economic and intellectual impacts. The first five Hijri centuries as example” - محمد زكي محمود اللهيبي, صالح (Al-Adab Journal, 2018)
This research deals with delicate topic that I think deserves to be researched, that it focuses on the economic position of Oman at the stage of early Islam and its impact on spreading Islam, and the enforcement of the Arabic-Islamic culture in large parts of the globe, especially in the Malay Archipelago, China, Africa and India.The importance of the research comes from being based on the descriptive and analytical explanation for an important group of resources, mainly the historical documents and texts that shows the Omani economic, cultural and civilizational role in the Islamic establishment phase, in the Arab region and in the world, it also shows the prestigious economic position that Oman had for several centuries which affected promoting the Arab and Muslim identity far from the Arab and Muslim world.The question that research seeks to address is to what extent the Omanis managed, through their global economic activity, to disseminate the Islamic religion, and the resulted cultural, social and other effects.I will be using the descriptive and analytical methods in this research to cover the subject from all its aspects working towards the required answers.The topics of the research will beas follows:The settlement of Omanis in the eastern shores of the Arabian Gulf and its strategic aspect.The world's most important commercial goods imported via Oman in early Islam.Omani marine and its economical and cultural impact.The economical and spiritual impact of Oman in India, the Malay Archipelago and China.The research will rely on number of primary sources, references and recent studies.